The Effect of Push-Up Training on Service Ability on Volyball - Arbain, Pedri; Jatra, Rices (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Service in volleyball is one of the early markers of the game. Aside from being a service marker, it is also one of the initial capital that can be done to get a point advantage in the volleyball game. The top serve is one of the most frequently used services by volleyball players. The purpose of the study was to find out how the effect of the push-up exercise on the success of the top serve in volleyball. Up to this study, there were 14 athletes from Sentajo Raya District. This study was a population study because all samples were the total population. The instrument used was to measure the ability to direct the service ball correctly and directionally which was carried out after the athletes were given the treatment given to the research subjects, which showed a value of t = -4329 with a significance value of 0.001 < 0.05. The results of the study revealed that if. The conclusion obtained is that there is a significant effect of the results of the push-up exercise on the ability to serve up in volleyball. do a push-up exercise model first. The data analysis technique used in this study was the paired sample t-test. The results obtained to determine the effect of push-up exercises on service ability